Rede Cegonha e saúde bucal: um panorama na região central do estado de São Paulo - Pereira, Carmen Lucia de Oliveira (2018)
Descriptive and exploratory study that analyzed oral health care in the Rede Cegonha of the 24 municipalities of the Regional Health Department III - DRS III / Araraquara, state of São Paulo. A survey of the number of pregnant women registered with SISPRENATAL in 2015 and 2016 was carried out; and the identification of potentialities and weaknesses in the oral health care path at Rede Cegonha. The information collected in the SISPRENATAL database and in the questionnaires received descriptive statistical treatment, while the information obtained from the interviews with the DRS-III articulators was subjected to thematic content analysis. In the cut off of the studied period, 17,959 pregnant women were registered in SISPRENATAL by the 170 health establishments that provide prenatal care in DRS-III. Pregnant women are predominantly white women aged 20 to 29 years old. The full management of municipalities is seen as a power, as it gives autonomy to build and implement contextualized actions, while the lack of protocols and flows is pointed out as the greatest weakness in comprehensive prenatal care. Considering that oral health care is transversal to the Health Care Networks, this study signals the need to strengthen oral health actions in the Rede Cegonha.